Drivers and barriers: proposal a new governance model (Deliverable 5.5, B-WaterSmart project) - Schmidt, Luísa (2023)
The present report corresponds to Deliverable 5.5 of B-WaterSmart – Drivers and barriers: proposal for a new governance model”. It Alicante (Spain), Bodø (Norway), East Frisia (Germany), Flanders (Belgium), Lisbon (Portugal), and Venice (Italy), according to the 12 OECD Principles for Water Governance (2015). It includes six dedicated chapters where we analyse what improvements in the current water governance models will drive more effective implementation of water-smart solutions across the fields of water reuse, sludge reuse, and stormwater management. The report includes This deliverable follows up on D5.3 – “Drivers and Barriers for Water-Smart Solutions across 6 European Cases: Policy and Governance”, submitted in M18 (February 2022) and concludes Task 5.2 on Drivers and Barriers for the Implementation of B-WaterSmart Solutions (M36). It will inform further work of WP5 – Society, Governance and Policy, namely Task 5.4 – Guidelines and recommendations for policy & regulation for water-smart systems.